Unravel melt pool and bubble dynamics during laser powder bed fusion of polyamides using synchrotron X-ray imaging and process simulation - Chu Lun Alex Leung; Jabbar Gardy; Mark Isaacs; Shashidhara Marathe; Michał M. Kłosowski; Junji Shinjo; Chinnapat Panwisawas; Peter D. Lee (Virtual and Physical Prototyping)
Laser powder bed fusion (LPBF) of Polyamide 12 (PA12) using a near-infra-red (NIR) beam is largely unexplored; therefore, the beam-matter interaction, evolution mechanisms of the melt pool and defects remain unclear. Here, we employed a combination of in situ synchrotron X-ray imaging, ex situ materials characterisation techniques, and high-fidelity process simulations to study these behaviours during LPBF of PA12. Our results demonstrate that the NIR absorption of PA12 can be improved by 600 times through powder surface modification with C, P and Al species. In situ X-ray images reveal that the PA12 powders undergo melting, viscous merging, volume expansion, warping, solidification, and shrinkage before forming a solid track. Our results uncover the bubble evolution mechanisms during LPBF of PA12. During laser scanning, the high-energy laser beam produces organic substances/vapours which are trapped inside bubbles during viscous merging. These bubbles continue to shrink due to vapour condensation as the polymer cools under a cooling rate range of 200 - 600 K s−1. Using the collected data, we have developed a data-driven bubble shrinkage criterion to predict the bubble shrinkage coefficient using the bubble half-life, improving the build quality of LPBF polymeric parts.